1985
DOI: 10.1021/j100257a006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electron correlation on the metal-ligand interaction in iron pentacarbonyl (Fe(CO)5)

Abstract: In the present work large-scale contracted CI calculations have been performed in order to investigate the bonding situation in Fe(C0)5. Near degeneracy correlation effects are shown to be mainly responsible for the failure of the Hartree-Fock model to correctly reproduce the metal-to-ligand distances (axial and equatorial) and the corresponding force constants. In addition, some aspects concerning the computational treatment of large transition-metal systems are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…One well‐documented critical case is that of metal‐CO complexes. At the HF level, the metal‐CO distances are calculated to be too long (Lüthi, Siegbahn, & Almlöf, 1985; Barandiaran et al, 1986) indicating that electron‐correlation effects are very important. However, in a study on Cr(CO) 6 complexes carried out by Barnes, Liu, & Lindh (1993) it was found that the inclusion of electron‐correlation effects yield CrCO distances still too long as compared with the experimental values.…”
Section: Performance Of the Modelmentioning
confidence: 99%
“…One well‐documented critical case is that of metal‐CO complexes. At the HF level, the metal‐CO distances are calculated to be too long (Lüthi, Siegbahn, & Almlöf, 1985; Barandiaran et al, 1986) indicating that electron‐correlation effects are very important. However, in a study on Cr(CO) 6 complexes carried out by Barnes, Liu, & Lindh (1993) it was found that the inclusion of electron‐correlation effects yield CrCO distances still too long as compared with the experimental values.…”
Section: Performance Of the Modelmentioning
confidence: 99%
“…A correct treatment of the correlation has been shown to be crucial for the geometry of first-row open-shell transition metal complexes (Langhoff & Bauschlicher, 1988, Lüthi et al, 1985, and it turned out to be equally important also for zinc complexes. When the Zn-S bond lengths were optimised at the MP2 level, the Zn-S bond lengths decreased by 6.8 pm to 241.5 pm.…”
Section: Influence Of the Ligand Choice Basis Set And Correlation Omentioning
confidence: 99%
“…One of the ®rst persons to point out these diculties was Jan AlmloÈ f, to whom this issue of the journal is dedicated. In a set of careful studies, mainly on ferrocene [10±12] and iron pentacarbonyl [13], he showed, at a time when calculations on this size of systems was extremely dicult, that electron correlation is of fundamental importance for these systems and also that very large basis sets are required even for a qualitatively correct description of structures. The direct SCF technique [14], invented and developed by Jan AlmloÈ f, was used extensively in these studies.…”
Section: Introductionmentioning
confidence: 99%